Trans-Cinnamic Acid Stimulates White Fat Browning and Activates Brown Adipocytes - Kang, Nam Hyeon (Nutrients, 2019)
Recently, pharmacological activation of brown fat and induction of white fat browning (beiging) have been considered promising strategies to treat obesity. To search for natural products that could stimulate the process of browning in adipocytes, we evaluated the activity of trans-cinnamic acid (tCA), a class of cinnamon from the bark of Cinnamomum cassia, by determining genetic expression using real time reverse transcription polymerase chain reaction (RT-PCR) and protein expression by immunoblot analysis for thermogenic and fat metabolizing markers. In our study tCA induced brown like-phenotype in 3T3-L1 white adipocytes and activated HIB1B brown adipocytes. tCA increased protein content of brown-fat-specific markers (UCP1, PRDM16, and PGC-1α) and expression levels of beige-fat-specific genes (Cd137, Cidea, Cited1, Tbx1, and Tmen26) in 3T3-L1 white adipocytes, as well as brown-fat-specific genes (Lhx8, Ppargc1, Prdm16, Ucp1, and Zic1) in HIB1B brown adipocytes. Furthermore, tCA reduced expression of key adipogenic transcription factors C/EBPα and PPARγ in white adipocytes, but enhanced their expressions in brown adipocytes. In addition, tCA upregulates lipid catabolism. Moreover, mechanistic study revealed that tCA induced browning in white adipocytes by activating the β3-AR and AMPK signaling pathways. tCA can induce browning, increase fat oxidation, reduce adipogenesis and lipogenesis in 3T3-L1 adipocytes, and activate HIB1B adipocytes, suggesting its potential to treat obesity.